2019
DOI: 10.2147/jpr.s196705
|View full text |Cite
|
Sign up to set email alerts
|

<p>Corneal subbasal nerve plexus changes in patients with episodic migraine: an in vivo confocal microscopy study</p>

Abstract: Background and purpose: It has been generally thought that activation and sensitization of the trigeminovascular system may contribute to the pathogenesis of migraine. Nevertheless, there is little evidence on abnormalities in peripheral trigeminal afferent nerves from humans in vivo. Alterations of corneal nerves from the ophthalmic branch of the trigeminal nerve may support the notion that trigeminal afferent nerves are involved in migraine pathophysiology. The aim of the present study was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
4
16
0
Order By: Relevance
“…CNFD and CNFL are reduced in patients with chronic migraine ( 19 ), especially those with photophobic migraine ( 20 ). However, in a recent study of patients with episodic migraine, nerve branching and tortuosity and Langerhans cell density were increased compared to controls, which are indicative of nerve regeneration and inflammation ( 21 ). In a recent study of patients with burning mouth syndrome, corneal nerve fiber density and length were lower and Langerhans cell density was higher compared to control subjects ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNFD and CNFL are reduced in patients with chronic migraine ( 19 ), especially those with photophobic migraine ( 20 ). However, in a recent study of patients with episodic migraine, nerve branching and tortuosity and Langerhans cell density were increased compared to controls, which are indicative of nerve regeneration and inflammation ( 21 ). In a recent study of patients with burning mouth syndrome, corneal nerve fiber density and length were lower and Langerhans cell density was higher compared to control subjects ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Corneal nerve fiber density (CNFD) and corneal nerve fiber length (CNFL) are reduced in patients with chronic migraine ( 19 ), especially those with photophobia ( 20 ), although a recent study has demonstrated increased corneal nerve branch density and tortuosity and Langerhans cells in patients with episodic migraine ( 21 ). We have recently shown a reduction in corneal nerve fiber density and length and an increase in Langerhans cell density in patients with burning mouth syndrome ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Corneal nerve branching and tortuosity were significantly increased in individuals with migraine compared to controls (91 ± 13.8 vs 75 ± 14.2 branches/mm 2 , p=0.03 and 2.3 ± 4.6 vs 1.6 ± 0.5, p=0.01, respectively). 73 Photophobia has also been linked to peripheral corneal nerve abnormalities. In a prospective Indian study, individuals with chronic migraine and photophobia (n=36) had significantly lower subbasal nerve parameters, including corneal nerve fiber length (14.8 ± 4.0 vs 18.1 ± 3.3 mm/mm 2 , p=0.007), compared to those with migraine but no photophobia (n=24).…”
Section: Dry Eye and Migraine Share Underlying Pathophysiologymentioning
confidence: 99%
“…Among the components of this avascular tissue, the nerves are of particular interest, as changes in their morphology and/or quantification serve as pointers towards understanding the presentation and progression of a wide range of not only keratopathies, but also neurovascular and neurodegenerative diseases. The characteristics of corneal nerves in systemic conditions associated with peripheral neuropathies such as diabetes, Fabry’s disease, Behçet’s and Parkinson’s disease have been studied [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%